Sosialisasi dan Edukasi Pencegahan Covid-19 Kepada Siswa Sekolah Dasar Negeri Cabi - Saifudin; Nizar Hidayat; Billy Rado; Fathul Jannah; Indrianto Rumapea; Megawati; Muhammad Ardhi Faddakiri; Nurul Jannah; Ummi Husna (Wadah Inovasi Indonesia, 2021)
The education sector has implemented online learning, but now face-to-face learning can be carried out again by following the rules and complying with health protocols. SDN Cabi, Simpang Empat District, Banjar Regency also conducts face-to-face learning activities. The activity begins on August 30, 2021 which is carried out in stages. The method used is by using learning methods through mind mapping media, simulations or direct practice to students, and forming new habits systematically or in accordance with the steps of application starting from home, entering the school environment, and leaving the school environment. This can become a habit for students and is more organized or systematic. The material presented consists of: (1) how to wash hands properly and correctly, and (2) provide explanations accompanied by posters about the importance of complying with the implementation of 6M, namely maintaining distance, wearing masks, washing hands, avoiding crowds, reducing mobility, and avoiding eating together.